Wolf Creek XVII Part 7: Mechanical circulatory support - Cindy H. Hsu; George Trummer; Jan Belohlavek; Demetris Yannopoulos; Jason A. Bartos (Resuscitation Plus, 2023)
Introduction: Failure to restore spontaneous circulation remains a major cause of death for cardiac arrest (CA) patients. Mechanical circulatory support, specifically extracorporeal cardiopulmonary resuscitation (ECPR), has emerged as a feasible and efficacious rescue strategy for selected refractory CA patients. Methods: Mechanical Circulatory Support was one of six focus topics for the Wolf Creek XVII Conference held on June 14–17, 2023 in Ann Arbor, Michigan, USA. Conference invitees included international thought leaders and scientists in the field of CA resuscitation from academia and industry. Participants submitted via online survey knowledge gaps, barriers to translation and research priorities for each focus topic. Expert panels used the survey results and their own perspectives and insights to create and present a preliminary unranked list for each category that was debated, revised and ranked by all attendees to identify the top 5 for each category. Results: Top 5 knowledge gaps included optimal patient selection, pre-ECPR treatments, logistical and programmatic characteristics of ECPR programs, generalizability and effectiveness of ECPR, and prevention of reperfusion injury. Top 5 barriers to translation included cost/resource limitations, technical challenges, collaboration across multiple disciplines, limited patient population, and early identification of eligible patients. Top 5 research priorities focused on comparing the outcomes of prehospital/rapid transport strategies vs in-hospital ECPR initiation, implementation of high-performing ECPR system vs standard care, rapid patient identification tools vs standard clinical judgment, post-cardiac arrest bundled care vs no bundled care, and standardized ECPR clinical protocol vs routine care. Conclusion: This overview can serve as an innovative guide to transform the care and outcome of patients with refractory CA.